The New Image Encryption and Decryption Using Quasi Group - Agarwal, Ankit; Varma, Amit; Kumar, Durgesh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Multimedia Communication is the new age of communication. Image Communication is one of the most popular types of multimedia communication. This type of communication always faces security challenges. Security breach is rising at a rapid rate. Image privacy is facing an even bigger threat. There are several image cryptography techniques having both positive and negative consequences. Via this paper, we are presenting a new approach for image encryption and decryption by using pixel shifting and using Quasigroup (Latin Square) without performing translation. It requires low computation as a key. Image pixel reshuffling is done randomly and in a non-repeated manner.